Valuation with share repurchases and personal taxes - Ralf Diedrich; Stefan Dierkes; Johannes Sümpelmann (Journal of Business Finance & Accounting, 2022)
We derive a consistent valuation approach that integrates the interdependent effects of cash dividends, share repurchases and active debt management while considering personal taxes. The valuation approach is based on the assumption that a predetermined proportion of the flow to equity is used for share repurchases instead of cash dividends. Additionally, we examine the effects of share repurchases on the cost of equity by deriving appropriate adjustment formulae. Furthermore, we run simulations to investigate the valuation differences caused by the distribution of excess cash via cash dividends or share repurchases. The results show that share repurchases have a significant positive effect on equity market value.
Keywords: 650; active debt management; cash dividends; cost of equity; equity market value; personal taxes; share repurchases; simulations; valuation